Peripartum cardiomyopathy: current understanding, comprehensive management review and new developments. Issue 1023 (10th October 2010) - Pyatt, Jason R; Dubey, Gopal
Abstract : Peripartum cardiomyopathy (PPCM) is a rare and potentially fatal disease which presents with symptoms of heart failure primarily due to left ventricular (LV) systolic dysfunction in the last month of pregnancy and up to 5–6 months after delivery. PPCM is still regarded as a disease of unknown aetiology, although recent evidence suggests a role for a 16 kDa prolactin derivative produced by proteolytic cleavage of prolactin secondary to unbalanced oxidative stress present during late pregnancy and early puerperium. The medical management of PPCM is similar to other forms of non-ischaemic dilated cardiomyopathy, but with the management tailored to choose safe drugs in pregnancy and lactation to minimise maternal and fetal morbidity. There is an increased risk of venous thromboembolism, and anticoagulation is recommended. About 30–50% of the patients recover without complications, with their baseline LV systolic function at rest returning to normal. The risk of recurrence of PPCM is high, especially if the LV systolic function has not fully recovered. However, for those women who have normal LV systolic function as demonstrated on echocardiography and dobutamine stress test, the risk of severe cardiomyopathy including death is relatively low in a subsequent pregnancy.